Perceptions of barriers and facilitators to early integration of pediatric palliative care: A national survey of pediatric oncology providers. Issue 6 (8th February 2018) - Dalberg, Todd; McNinch, Neil L.; Friebert, Sarah
Abstract: Objectives: The goal of this study was to assess pediatric oncology providers' perceptions of palliative care in order to validate previously identified barriers and facilitators to early integration of a pediatric palliative care team (PCT) in the care of children with cancer. Methods: A 36‐question survey based on preliminary, single‐institution data was electronically distributed to pediatric oncology physicians, nurse practitioners, nurses, and social workers nationally. The principal outcomes measured included perceived barriers and facilitators to early integration of pediatric palliative care. Data were analyzed using Rv3.1.2 statistical software. Results: Most respondents agreed that the PCT does not negatively impact the role of the oncologist; however, there were concerns that optimal patient care may be limited by pediatric oncologists' need to control all aspects of patient care ( P < 0.001). Furthermore, oncologists, more than any provider group, identified that the emotional relationship they form with the patients and families they care for, influences what treatment options are offered and how these options are conveyed ( P < 0.01). Education and evidence‐based research remain important to all providers. Respondents reached consensus that early integration of a PCT would provide more potential benefits than risks and most would not limit access to palliative care based on prognosis. Conclusions: Overall, providers endorse early integration of the PCT for children with cancer. There remains a continued emphasis on provider and patient education. Palliative care is generally accepted as providing a benefit to children with cancer, though barriers persist and vary among provider groups.